2021
DOI: 10.12998/wjcc.v9.i31.9564
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of primary giant cell tumor in soft tissue on magnetic resonance imaging: A case report

Abstract: BACKGROUND Primary soft tissue giant cell tumor (GCT-ST) is rare and has relatively low malignant potential. Most reports are pathological and clinical studies, while imaging studies have only been reported in cases of adjacent bone or with atypical cystic degeneration. With regard to the findings on magnetic resonance imaging (MRI) or ultrasonography, superficial masses can be further identified based on facial edema, skin thickening, skin contact, internal hemorrhage or necrosis and lobulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Previous studies have suggested that CT images of GCT-ST usually show a low-density tumor. MRI images mostly showed low-isointense on T1WI and hyperintense on T2WI [6], which are intensely heterogeneous enhancements on post-contrast T1WI. Internal areas without enhancement are often found due to necrosis, cystic degeneration and fibrous tissue [7].…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have suggested that CT images of GCT-ST usually show a low-density tumor. MRI images mostly showed low-isointense on T1WI and hyperintense on T2WI [6], which are intensely heterogeneous enhancements on post-contrast T1WI. Internal areas without enhancement are often found due to necrosis, cystic degeneration and fibrous tissue [7].…”
Section: Discussionmentioning
confidence: 95%
“…Color Doppler examination may display increased vascularity [14,18]. Computed tomography (CT) shows a solid, heterogeneous, predominantly hypodense mass [8,[18][19][20][21]. Contrast-enhanced CT demonstrates heterogeneous enhancement.…”
Section: Imaging Featuresmentioning
confidence: 99%
“…Contrast-enhanced CT demonstrates heterogeneous enhancement. On magnetic resonance imaging (MRI), GCTST usually shows a solid soft tissue mass with low to intermediate signal intensity on T1-weighted images and variable signal intensity on T2-weighted images [8,14,20]. On the other hand, An et al reported one case of GCTST displaying a predominantly cystic mass [15].…”
Section: Imaging Featuresmentioning
confidence: 99%
“…The diameter ranges from 0.7 to 10.0 cm [35][36][37]. Using MRI, GCTST usually reveals a solid soft tissue mass with low to intermediate signal intensity on T1weighted images, variable signal intensity on T2-weighted images, and avid enhancement following contrast administration [38][39][40]. Positron emission tomography (PET) imaging demonstrates increased fluorodeoxyglucose (FDG) uptake with high standard uptake values [38].…”
Section: Differential Diagnosismentioning
confidence: 99%